The Place of Money in History - Christopher Muellerleile (The Sage handbook of historical geography, 2020)
Money is a precarious and abstract embodiment of value, and while there is more money in motion around the globe than ever before, the basic problem has not changed since its earliest use in antiquity. That is, money’s value must be actively, and at times forcefully maintained across time and space. The chapter provides a selected overview of the historical geography of money, but it also considers why a historical geographic analysis is crucial to understanding contemporary money and its politics. It argues that throughout history various money forms have been dependent upon political power and the maintenance of territory. While it may be tempting to lean on contemporary concepts such as financialization to explain the power and politics of money, this chapter makes the case that a more historical and geographically sensitive analysis is more fruitful. Without a doubt, there is uniqueness to the political economy of 21st century financial geographies, but the chapter argues that even the most recently developed money form, cryptocurrency, is better understood in a historical geographic context.